2016
DOI: 10.1016/j.jiec.2015.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Potential and performance of a polydopamine-coated multiwalled carbon nanotube/polysulfone nanocomposite membrane for ultrafiltration application

Abstract: The addition of multiwalled carbon nanotubes (MWNTs) as inorganic fillers is well known to improve membrane performance for water desalination. Most MWNTs are treated by acid treatment to enhance their hydrophilicity before their applications in membranes. However, acid treatment leads to structural damages of the MWNT wall. An alternative way of improving the hydrophilicity of MWNTs is through coating of polydopamine (Pdop), where MWNT wall damage is avoided. In the present study, polydopamine-coating on MWNT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(46 citation statements)
references
References 67 publications
2
44
0
Order By: Relevance
“…The PSf/IONPs membrane demonstrates better PWP due to the improved hydrophilicity and porosity of the membrane. The increased number of finger‐like structures and pore distribution promote greater water passage through the membrane . Also, the large surface area of the IONPs provides extra room needed to promote membrane contact with pure water .…”
Section: Resultsmentioning
confidence: 99%
“…The PSf/IONPs membrane demonstrates better PWP due to the improved hydrophilicity and porosity of the membrane. The increased number of finger‐like structures and pore distribution promote greater water passage through the membrane . Also, the large surface area of the IONPs provides extra room needed to promote membrane contact with pure water .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, polydopamine‐based nanocomposite membranes have been exploited to enhance ultrafiltration performance. This includes incorporation of carbon nanotubes, gold nanorods, silica particles, and silver nanoparticles into membranes used to reduce oil, protein, and bacterial fouling in wastewater filtration.…”
Section: Applications Of Catecholamine Polymersmentioning
confidence: 99%
“…This has led to the fillers improving various physical properties of the final composites. For example, polycatecholamines have been used to bind reinforcing agents (boehmite nanoparticles, barium titanate nanoparticles, halloysite nanotubes, silver nanoparticles, short Kevlar fibers, bioactive glass particles, glass fiber, carbon fiber, reduced graphene oxide, and carbon nanotubes) to the bulk polymer to improve mechanical properties. Other examples include polydopamine coated boron nitride nanoparticles and carbon nanotubes used to improve composite thermal conductivity; polydopamine coated halloysite nanotubes, used to enhance the proton conductivity of proton exchange membranes; polydopamine coated metallic nanoparticles used to increase electrical conductivity; and polydopamine used to incorporate carbonyl iron microparticles and magnetite nanoparticles into composites used for microwave absorption.…”
Section: Applications Of Catecholamine Polymersmentioning
confidence: 99%
“…Carbon nanotube (CNT) incorporated membranes have attracted great interest as an important technique for membrane surface hydrophilicity modification since they have functional groups containing oxygen that improve membrane permeability . A number of research studies have discussed the antifouling effect of CNTs and have shown their excellent antimicrobial ability, hydrophilicity and anti‐biofouling properties, and their considerable impact on improving permeability . Moreover, CNTs last longer than traditional nanoparticles …”
Section: Fouling Control Strategiesmentioning
confidence: 99%